A new glandular Mimosa species from Southern Brazil and insights about its glandular trichomes micromorphology - Silveira, Fernanda Schmidt; Vargas, Wanderleia de [UNESP]; Fortuna-Perez, Ana Paula [UNESP]; Sfoggia Miotto, Silvia Teresinha (Soc Botanica Brasil, 2019)
Mimosa baptistae is a new species presenting stalked glandular trichomes that give it a glutinous appearance, mainly with respect to the leaflets. Furthermore, it is an aculeate species, with multijugate leaves, white stamens, and fruits also covered by glandular trichomes. A herbaria survey and fieldwork only recorded this species as occurring on sandstone outcrops of the city Cacapava do Sul, Brazil. The species may be confused with other species of Mimosa sect. Batocaulon ser. Stipellares such as M. bifurca, M. sobralii and M. lepidota. However, features such as absence/presence of aculei, stamens color, habitat, and flower features are useful for distinguishing them from the new species. Here, we provide notes on morphology, geographic distribution, as well as anatomical detail of its glandular trichomes and content. Finally, we discussed the taxonomic significance of the micromorphology of glandular trichomes and their content in Mimosa ser. Stipellares as well as the potential applicability of such features to better understand the morphology of this series.
Keywords: glands; leaflets; Pampa; secretory structures; Serra do Sudeste